Ristocetin in the Diagnosis of von Willebrand’s Disease: A Comparison of Rate and Percent of Aggregation with Levels of the Plasma Factor(s) Necessary for Ristocetin Aggregation - Dowling, S. V; Muntz, R. H; D’Souza, S; Ekert, H (Thrombosis and Haemostasis, 1975)
Percent aggregation and the aggregation rate of platelet rich plasma (PRP) in response to ristocetin (1.75 mg/ml) were measured in 20 normals and 16 patients with von Willebrand’s disease (vWd), with and without the addition of acetylsalicylic acid (ASA). Percent aggregation did not clearly distinguish between normals and patients with vWd. Aggregation rate was normal in only 2 of 16 patients, and after incubation of PRP with ASA 1 of these 2 remained normal.The corrective effect of dilutions of platelet poor plasma (PPP) on the ristocetin response of washed platelets (von Willebrand’s factor, vWf ) was measured in 21 normals and 12 patients with vWd. All patients with vWd had abnormal levels. There was a significant correlation between aggregation rate and vWf in patients with vWd but not in normals. Both tests appear to measure closely related defects, and the aggregation rate is as specific as the vWf level for the diagnosis of clinically affected patients.